Analyzing the Impact of Hybrid Learning on Modern Curriculum and Material Development - Fathiyyah Fahira Syarifuddin Fathiyyah Fahira Syarifuddin; Selnistia Hidayani Selnistia Hidayani; Farah Zulfa Azzahro Farah Zulfa Azzahro (Mathematics Education Study Program, 2025)
The increasing adoption of hybrid learning has brought significant changes to contemporary educational practices, particularly in curriculum design and learning material development. This study examines how hybrid learning environments influence the structure, flexibility, and delivery of modern curricula. By integrating face to face instruction with digital learning platforms, hybrid learning encourages a shift from rigid, content-oriented curricula toward more adaptive and learner-centered models. The findings highlight that hybrid learning supports the alignment of learning objectives with diverse student needs, promotes independent learning, and enhances instructional effectiveness through varied learning modalities. Furthermore, the development of learning materials within hybrid systems demonstrates a growing reliance on multimedia resources, interactive content, and digital accessibility. These materials are designed not only to convey knowledge but also to foster engagement, critical thinking, and continuous learning beyond the classroom. Despite challenges related to technological readiness and instructional consistency, hybrid learning offers substantial opportunities for curriculum innovation and material enrichment. Overall, this study suggests that hybrid learning plays a crucial role in reshaping modern education by encouraging curricular flexibility and more responsive material development suited to the demands of the digital era.